DETECTION AND EXTRACTION OF ANTI-LISTERIAL COMPOUNDS FROM CALLIGONUM COMOSUM, A MEDICINAL PLANT FROM ARID REGIONS OF TUNISIA - Riadh, Hammami; Imen, Farhat; Abdelmajid, Zouhir; Sinda, Fedhila (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Calligonum comosum, a Tunisian plant from arid regions, is traditionally used in folk medicine to treat rural population microbial infections. The plant was investigated in vitro for its ability to inhibit the growth of Listeria ivanovii. Various aqueous and organic extracts were prepared from different plant tissues. Results indicated that ethanolic, methanolic and acetonic extracts from whole plant tissues except seeds, exhibited significant antibacterial activity with growth inhibition zones (9 - 18mm) as shown by the agar-well diffusion method. Minimum Inhibitory Concentration (MIC) of 0.65mg/ml was obtained in acetonic extract generated from C. comosum roots. Preliminary phytochemical analysis based on heat and protease treatments showed that bioactive extracts were stable up to 10m in heating at 100Â°C and that they resist protease digestion. Based on these latter results, the activity of organic extracts may be related to the presence of sterols, terpenoids, and/or phenolics. Overall, these results indicate that C. comosum organic extracts are probably useful in the control of food contamination by listerial species.